Analisis Pengaruh Perputaran Kas, Perputaran Piutang dan Perputaran Persediaan Terhadap Profitabilitas Pada Sub Sektor Makanan dan Minuman Yang Terdaftar di Bursa Efekk Indonesia Pada Tahun 2018-2022 - Ismi Khoerunisah; Rakhmat; Surtini (Sekolah Tinggi Ilmu Ekonomi Mulia Pratama, 2024)
This research was conducted with the aim of analysing the effect of cash turnover accounts receivable turnover and inventory turnover profitability in food and beverage sub-sector companies listed on the Indonesia stock exchange in 2018-2022 The method used was purposive sampling with a total sampel 7 sampple (5 periods) of good and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange out of a total population of 35 populations. Data analysis used multiple linear analysis methods, analysis of the coefficient of determination, ftest using SPSS version 26. From the result of multiple linear regression analysis, the regression equation Y=4,475 + 0,034 (X1) + 0,020 (X2) + 0,315 (X3) shows that the regression coefficient for the cash turnover variabel (X1) is 0,034. This means that if cash turnover increases by one unit, it will have an impact pn profitability of 0,034. For the receivables turnover (X2) it is 0,020. This means that if receivables turnover increases by one unit, it will have an impact on profitability of 0,20. For the inventory turnover variable (X3) it is 0,315. This means that if inventory turnover increases by one unit, it will have an impact on profitability of 0,315. From the results of three coefficients, the independent variable that has the most dominant influence on the dependent variable is the inventory turnover variable with a value of 0,315. The result of this study are cash turnover, accounts receivable turnover and inventory turnover and simultaneous effect on profitability, the influence of cash turnover receivable turnover and inventory turnover does not partially affect profitability. Adjusted R2 Square value is 0,276 which means that the ability of the three independent variables can effect profitability by 27,6% while the rest is influenced by other factors.